Suara Profetik Nabi Amos sebagai Dasar Teologis dalam Merespons Konflik Lahan - Riecha Priyadi Fhany Damanik; Sari Asi Situmorang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
The land conflict in Pandumaan-Sipituhuta, Humbang Hasundutan, was triggered by the granting of concessions by TPL that ignored the customary rights of communities who had managed the incense forest for generations. The church played an important role in advocating for justice through a prophetic pastoral approach, fighting for the rights of marginalized indigenous peoples and condemning the structural injustices that occurred. The church adheres to biblical teachings, such as those in the book of Amos, which call for social justice, as well as fighting for environmental preservation and the protection of customary rights. This study uses qualitative research in a prophetic pastoral approach. The results of this review show that the church is involved in documenting customary land to prove the legality of indigenous peoples' rights and acts as a mediator between the community and the government. Through prophetic pastoral care, the church voices the importance of respecting the rights of indigenous peoples and demands social change in accordance with God's will.